GERIATRICIAN PERSPECTIVES ON THE MANAGEMENT OF MILD COGNITIVE IMPAIRMENT/MILD ALZHEIMER'S DISEASE. (20th December 2022) - Gopalakrishna, Ganesh; Pruzin, Jeremy; Alford, Susan; Hamersky, Carol; Sabharwal, Anup; Brunton, Stephen
Abstract: Mild cognitive impairment (MCI) and Alzheimer's disease (AD) dementia are characterized by cognitive impairment and in AD a progressive functional impairment. This study sought to understand the role of geriatricians in treating patients with MCI/mild AD dementia. An anonymous, online survey was conducted in the US with 301 healthcare professionals (HCPs), including 75 primary care providers who practice as board certified geriatricians, and treat ≥10 patients per month with MCI/mild AD dementia. Geriatricians reported that among their patients with MCI/mild AD dementia, they initially make this diagnosis 70% of the time. Geriatricians reported that the topics commonly discussed with patients at the time of diagnosis are treatment options (85%), care management strategies (81%) and disease progression (80%). When referring patients to other specialties for treatment, geriatricians most often referred to neurologists (41%). Most (83%) geriatricians considered themselves the coordinator of care for patients with MCI/mild AD dementia; however, only 5% of non-geriatrician HCP respondents view geriatricians as such. Geriatricians reported prescribing/recommending treatments for ongoing management of MCI/mild AD dementia, with the most common being mental exercises (76%), acetylcholinesterase inhibitors (75%), social interaction (73%), medications to manage comorbidities (72%), and lifestyle improvements (72%). Most (76%) geriatricians have received advanced formal training in MCI/mild AD dementia care with the majority (84%) expressing that they feel very confident in managing patients with MCI/mild AD dementia. Geriatricians are specialists that are well trained and confident in diagnosing, treating, and managing patients with MCI/mild AD dementia.